Novel approach to diagnosis of His bundle capture using individualized left ventricular lateral wall activation time as reference - Jastrzębski, Marek; Moskal, Paweł; Kukla, Piotr; Bednarek, Agnieszka; Kiełbasa, Grzegorz; Rajzer, Marek; Curila, Karol; Vijayaraman, Pugazhendhi (Journal of cardiovascular electrophysiology, 2021)
BACKGROUND: During nonselective His bundle (HB) pacing, it is clinically important to confirm His bundle capture versus right ventricular septal (RVS) capture. The present study aimed to validate the hypothesis that during HB capture, left ventricular lateral wall activation time, approximated by the V6 R-wave peak time (V6 RWPT), will not be longer than the corresponding activation time during native conduction. METHODS: Consecutive patients with permanent HB pacing were recruited; cases with abnormal His-ventricle interval or left bundle branch block were excluded. Two corresponding intervals were compared: stimulus-V6 RWPT and native HB potential-V6 RWPT. The difference between these two intervals (delta V6 RWPT), which was diagnostic of lack of HB capture, was identified using receiver operating characteristic (ROC) curve analysis. RESULTS: A total of 723 electrocardiograms (ECGs) (219 with native rhythm, 172 with selective HB, 215 with nonselective HB, and 117 with RVS capture) were obtained from 219 patients. The native HB-V6 RWPT, nonselective-, and selective-HB paced V6 RWPT were nearly equal, while RVS V6 RWPT was 32.0 (±9.5) ms longer. The ROC curve analysis indicated delta V6 RWPT > 12 ms as diagnostic of lack of HB capture (specificity of 99.1% and sensitivity of 100%). A blinded observer correctly diagnosed 96.7% (321/332) of ECGs using this criterion. CONCLUSIONS: We validated a novel criterion for HB capture that is based on the physiological left ventricular activation time as an individualized reference. HB capture can be diagnosed when paced V6 RWPT does not exceed the value obtained during native conduction by more than 12 ms, while longer paced V6 RWPT indicates RVS capture.
Keywords: blokáda Tawarova raménka; electrocardiogram; nonselective pacing; Bundle of His; Heart Ventricles; His bundle pacing; Bundle-Branch Block; kardiostimulace umělá; Cardiac Pacing, Artificial; Humans; lidé; loss of capture; srdeční komory; Electrocardiography; Hisův svazek; elektrokardiografie